Solidarity and the New Inequality. Issue 2 (30th May 2019) - Weithman, Paul
Abstract: Economists now have the data to generate a high‐resolution picture of the economic inequalities within the very top fractions of income and wealth and between the top‐most fractions and others that have emerged since the early 1980s. I shall refer to these inequalities collectively as "the new inequality." I argue that the moral value of solidarity can be used to raise pointed moral questions about the new inequality. In most cases, however, I shall raise such questions without answering them. For I contend that solidarity functions more usefully as part of an articulate hermeneutic of suspicion—that is, as a central element in skepticism about economic inequalities and their justifications. Seeing that it functions in this way, we can see one contribution religious ethics makes to an inquiry into the new inequality.